A Novel Scoring System Associated With Surgical Outcome of Distal-type Cervical Spondylotic Amyotrophy. Issue 9 (November 2017) - Funaba, Masahiro; Kanchiku, Tsukasa; Imajo, Yasuaki; Suzuki, Hidenori; Yoshida, Yuichiro; Nishida, Norihiro; Fujimoto, Kazuhiro; Taguchi, Toshihiko
Abstract : Study Design: A single-center retrospective study. Objective: To elucidate the pathology of distal-type cervical spondylotic amyotrophy (CSA) and to assess predictive factors and a novel scoring system associated with surgical outcome. Summary and Background: Because of its rarity, the pathophysiology and surgical outcome of distal-type CSA are less well understood compared with proximal-type CSA. Method: Surgical procedures were performed in 13 patients with distal-type CSA. Patients were classified into 2 groups: those with good recovery of muscle power (group 1, n=4) and those with fair recovery (group 2, n=9). All patients underwent magnetic resonance imaging. Central motor conduction time was recorded in abductor digit minim and compound muscle action potentials (CMAPs) were recorded in extensor carpi dig. Predictive factors associated with surgical outcome and a scoring system based on clinical, radiologic, and electrophysiological findings were evaluated. Twelve of 13 patients were scored for the following features: (1) duration of symptoms ≥13 months, (2) initial manual muscle testing ⩽1, (3) multiple compressions in magnetic resonance imaging, (4) CMAPs amplitudes on affected side <1 mV, (5) CMAPs amplitudes on normal side <7.2 mV, (6) central motor conduction time longer than 7.4 ms, (7) the ratio of CMAPs amplitudes comparison with the normal side <50%. Result: At final follow-up, 2 patients were graded excellent, 2 good, 9 fair, and 0 poor. None of the predictive factors was significantly different between groups 1 and 2. The mean score in group 2 (5.12±1.12) was significantly higher than for group 1 (2±1.15; P =0.006). Although all 8 patients in group 2 scored ≥4 points, all 4 patients in group 1 scored ⩽3. Conclusions: Comprehensive assessment using a scoring system is useful for predicting the surgical outcome of distal-type CSA. Surgeons should be aware that a score of ≥4 points correlates with poor surgical outcome on motor function.